Characterization and utilization of azolla pinnata with decanter cake waste as poultry feed - Zafirah Mohd Halim
Decanter cakes are the major wastes in crude palm oil industry which are currently disposed in the landfill or reuse as other applications. But on the other view, decanter cake is source of nutrients for producing bio-compound fertilizer and also suitable for animal food. In addition, Azolla pinnata comprises of significant high food value with a good proportion of protein, vitamins, and minerals. Therefore, the purpose of this project is to produce low-cost animal feed pellet by combination of Azolla pinnata (AP) with Decanter Cake (DC) at selected ratio. The proximate composition analysis of carbohydrate and protein in the pelletized AP and DC were analysed. In this study, 18 chicks at the age of 4 weeks were reared in six treatments, labelled control, T1 to T5, by substituting 0% (only maize), 100%, 95%, 90%, 85%, and 80% of Azolla pinnata protein (dry matter basis) respectively for 29 days. The specific growth rate of chicks were measured daily. There were not significantly varied between the chicks reared completely with maize and 95% substitution with A. pinnata. However, a significantly higher weight was gained for chicks reared in T5 than other treatments. The poorest performance was observed in chicks fed completely with Azolla pinnata, at control and T4. Based on the results, pellet made of ratio 20% of decanter cake and 80% of Azolla could be substituted with maize without significantly lowering their growth and product quality. As a conclusion, the poultry feed formulated of Azolla pinnata and decanter cake able to improve the weight of chicks. This feed pellet can be used as an alternative food source for poultry industry in Malaysia.